The Effectiveness of Classical Guidance Service of the Cooperative Learning Model of Game Tournament Type (TGT) in Increasing Student Learning Motivation - Puspa Devi, Ayu; Neviyarni, Neviyarni (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Learning motivation is an internal drive that plays a crucial role in determining students academic achievement. To enhance this motivation, one effective strategy is the use of classical guidance services with the cooperative learning model, specifically the team game tournament (TGT) type. This study aims to: (1) analyze differences in students' learning motivation before and after receiving classical guidance services using the TGT model, (2) compare the learning motivation between the experimental group and the control group, and (3) assess the effectiveness of special treatment on the experimental group compared to the control group without such treatment. This research employed a quantitative approach using a quasiexperimental design. The population consisted of 334 students at SMP Negeri 1 Rengat, with a sample of 63 students selected through purposive sampling. A Likertscale questionnaire was used as the instrument to measure students' learning motivation. Data were analyzed using nonparametric statistical tests, including the Wilcoxon test and the Mann Whitney U test, with the aid of SPSS version 20. The results indicate a significant improvement in the learning motivation of students in the experimental group after receiving classical guidance services based on the TGT model. Furthermore, there was a significant difference between the experimental and control groups, with the experimental group achieving a higher average posttest score. Thus, classical guidance services using the cooperative learning model, specifically the team game tournament type, are proven to be effective in enhancing students' learning motivation.